2012
DOI: 10.1523/jneurosci.0445-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Irregular Breathing in Mice following Genetic Ablation of V2a Neurons

Abstract: Neural networks called central pattern generators (CPGs) generate repetitive motor behaviors such as locomotion and breathing. Glutamatergic neurons are required for the generation and inhibitory neurons for the patterning of the motor activity associated with repetitive motor behaviors. In the mouse, glutamatergic V2a neurons coordinate the activity of left and right leg CPGs in the spinal cord enabling mice to generate an alternating gait. Here, we investigate the role of V2a neurons in the neural control of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
76
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(80 citation statements)
references
References 58 publications
3
76
0
1
Order By: Relevance
“…Studies have also shown that RA activates the expression of bHLH transcription factors to control the differentiation of neuronal cell types, such as V2a interneurons [44]. We hypothesized that by decreasing RA concentration we could promote the differentiation of V2a interneurons found rostrally in respiratory columns of the medial reticular formation of the hindbrain [14]. Our experiments showed that decreasing RA concentration increased Chx10 expression.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…Studies have also shown that RA activates the expression of bHLH transcription factors to control the differentiation of neuronal cell types, such as V2a interneurons [44]. We hypothesized that by decreasing RA concentration we could promote the differentiation of V2a interneurons found rostrally in respiratory columns of the medial reticular formation of the hindbrain [14]. Our experiments showed that decreasing RA concentration increased Chx10 expression.…”
Section: Discussionmentioning
confidence: 66%
“…V2a interneurons have been shown to be involved in repetitive motor behaviors in the CPGs of the spinal cord and medial reticular formations of the hindbrain and play an important role in left-right coordination of locomotion, skilled reaching movements, and rhythmic patterning of breathing [10,14,26]. Differentiation of V2a interneurons from mESCs has the potential to increase understanding developmental pathways and possibly provide a source for cell therapies in high cervical spinal cord injuries affecting respiratory and motor function.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ainsi, les souris transgéniques déficientes pour le gène Vglut2 ne survivent pas à la naissance et leur CPB est inactif in vitro [35]. L'ablation génétique d'une sous-population de ces neurones (les neurones V2a) n'abolit pas le rythme du CPB, mais le rend irrégulier [36]. Par ailleurs, il existe une sous-population de neurones glutamatergiques du CPB qui exprime la somatostatine et semble critique pour la respiration de l'adulte [24].…”
Section: Le Récepteur Nk1unclassified